Moving targets: Carbon pricing, energy markets, and social movements in Australia - Pearse, Rebecca (Environmental Politics, 2016)
Reporting on the origins and directions of social movement strategy on climate and energy issues in the last decade, the shifts in ‘climate movement’ practice are discussed using a neo-Polanyian account of the political economy of climate change combined with sociological analysis of the strategic decisions campaigners reported making. Since the mid-2000s, Australia’s climate movement has been engaged in three concurrent arenas of political contestation. The longest-standing arena of movement activity has been negotiations over climate policy. More recently, activists and communities are engaged in a struggle over the expansion of fossil fuels. A third contest has been waged over the present and future position of renewable energy technologies in Australia’s electricity market. In the wake of climate policy failure, energy campaigns have been deepened, and it seems that a broader energy justice agenda is being forged. New strategic dilemmas are visible in the field.
Environmental Studies; Education
Keywords: Australia; carbon pricing; climate policy; climatic changes; economics; energy industries; energy markets; fossil fuels; renewable energy sources; social movements

The Copenhagen Turn in Global Climate Governance and the Contentious History of Differentiation in International Law - McGee, Jeffrey; Steffek, Jens (Journal of Environmental Law, 2016)
The 2009 Copenhagen Accord marked a significant shift in global climate governance which has been substantially adopted in the 2015 Paris Agreement. At Copenhagen, binding targets for states to reduce emissions were replaced by voluntary pledges. We argue that the Polanyian 'double movement' offers a useful lens to understand the Copenhagen shift in global climate governance as part of ongoing contestation in the international law system between principles of economic liberalisation and redistributive intervention. In the second half of the 20th century, redistributive design of international legal institutions became evident in a number of issue areas including trade law, oceans law and the seminal climate treaties. However, there has been ongoing US lead opposition to 'redistributive multilateralism' (RM), particularly over the last decade of climate negotiations. The Copenhagen model of voluntary pledges, therefore, needs to be viewed as an outcome of this opposition to RM and a related weakening of differentiation in international environmental law.
Law; Environmental Studies
Keywords: Copenhagen; Copenhagen Accord; UNFCCC; climate change; differentiation of duties; environmental justice; environmental law; international cooperation; international law; political economy; regime design

Economy, Society and Earth in Polanyian and Wild Law Perspectives on Environmental Regulation: To Perform a Double or Triple Movement? - Pontin, Ben (Journal of Environmental Law, 2016)
Law; Environmental Studies
Keywords: BURDON; Peter D.; HAINES; Fiona; LANGE; Bettina; MALONEY; Michelle; Regulatory Transformations: Rethinking Economy-Society Interactions (Book); THOMAS; Dania; Wild Law: In Practice (Book); book review; double movement; environmental law; nonfiction; triple movement